THE USE OF READING PRACTICE VIDEO ON YOUTUBE TOWARDS STUDENTS ENGLISH PRONUNCIATION AT 10TH GRADE OF SMKN 7 KOTA SARANG - Shania, Egga; Syafrizal, Syafrizal; Handayani, Ika (Peneliti.net, 2024)
This research is aimed to find out any significance effect of Reading Practice Video on YouTube toward student’s English pronunciation at the tenth grade of SMKN 7 Kota Serang. This research used a quantitative research method by implementing a quasi-experimental design. The population of the research was the tenth-grade students of SMKN 7 Kota Serang in academic year 2023/2024. It consist of 380 students. This study used sample size of 30 students from each of two classes: an experimental class and a control class. The samples were selected by cluster sampling. Pre-test was given to both classes at the first meeting and then the post-test at the last meeting. To find the effect, the post-test was provided to both classes. The higher results achieved by the experimental group, which is 88.87. This result is significantly different from the control group, which is 83.03. Based on the scores of student’s pronunciation learning analysis by Independent Samples T-test. It was verified by the value of sig. (2-tailed) was 0.001<0.05. It can be concluded that the Null Hypothesis (H0) is rejected and the Alternative Hypothesis (Ha) is accepted. To conclude, using Reading Practice Video on YouTube has a significance effect toward student’s English pronunciation at the tenth grade of SMKN 7 Kota Serang.